Effects of Etco2 on the Minimum Alveolar Concentration of Sevoflurane that Blunts the Adrenergic Response to Surgical Incision: A Prospective, Randomized, Double-Blinded Trial. (16th June 2022) - Wu, Zhijie; Yu, Junjie; Zhang, Tianhua; Tan, Hongying; Li, Huiting; Xie, Lan; Lin, Wenqian; Shen, Danping; Cao, Longhui
Abstract : BACKGROUND: CO2 has anesthetic potency and effectively influences the circulatory system. We investigated the effects of Etco 2 on the minimum alveolar concentration of sevoflurane that blunts the adrenergic response to surgical incision (MAC-BAR) in patients undergoing radical surgery for gastric carcinoma. METHODS: Ninety patients undergoing radical gastric-carcinoma surgery under general anesthesia were enrolled and randomly assigned into 3 groups. After intubation, the Etco 2 in group L (n = 30), group N (n = 30), and group H (n = 30) was adjusted to 25 mm Hg ≤ Etco 2 <30 mm Hg, 30 mm Hg ≤ Etco 2 < 40 mm Hg, and 40 mm Hg ≤ Etco 2 < 45 mm Hg, respectively, by changes in controlled ventilation. Hemodynamics and depth of anesthesia were observed before and after skin incision. The MAC-BAR of sevoflurane for each group was determined using an up-and-down sequential-allocation technique. RESULTS: To obtain 7 crossovers, 25, 26, and 26 patients were used in group L, group N, and group H, respectively. The MAC-BAR of sevoflurane using the up-and-down method for group H was significantly lower than that for group L (2.3% [95% confidence interval CI, 2.2–2.4] vs 2.9% [95% CI, 2.7–3.0]; difference, −0.6% [95% CI, −0.7 to −0.4], P < .001) and group N (2.3% [95% CI, 2.2–2.4] vs 2.8% [95% CI, 2.8–2.9]; difference, −0.5% [95% CI, −0.7 to −0.4], P < .001), while no significant difference was found between group L and group N ( P = 1.000). CONCLUSIONS: Higher Etco 2 levels (Etco 2 values equal to 40 mm Hg or higher) can effectively decrease the MAC-BAR of sevoflurane in patients undergoing radical surgery for gastric carcinoma. Abstract :